Opinions of Thai University Students Towards Sneaker Experiential Advertising - Photisuvan, Napat (Dusit Thani College Journal, 2020)
This research aims to examine personal and psychological factors ,composed of beliefs, values, learnings, motives perceptions, reference groups and influence groups, opinions towards sneakers experiential advertising of Thai university students and compare opinions among groups with differences in personal and psychological data. A campus intercept survey was conducted at Rajamangala University of Technology Thanyaburi, with 328 students who voluntarily completed questionnaires in the first semester. Both descriptive statistics; frequency; mean, standard deviation and inferential statistics; independent t-test and one-way ANOVA were employed for data analysis. Findings were: 1) highest mean scores; learning that product well before purchasing, motive of purchasing was necessity, 2) students seemed to favor much on sense experiences higher than others. 3) comparisons showed statistically significant difference of mean scores of opinions towards experiential advertising between groups with different personal and psychological data. This research contributes to the literature on experiential advertising and also on unique characteristics of Thai university students on sneaker experiential advertising. Practical implications for advertising agents in Thailand, suggesting that they should concern more on these uniqueness characteristics of Thai university students in creating experiential sneaker advertising.